Fossil Myriapod Trails In the Permo-Carboniferous Strata of Northern Nova Scotia, Canada - Ryan, R. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1986)
Several new localities of the trace fossil, 01 pi Ichnites, have been found In the Perao-Carbonlferous strata of northern Nova Scotia. The tral Is at Cape John, Pictou County, Nova Scotia are the largest and the youngest (Early Pen Ian) record to date of this Ichnogenus attributed to myrlapods. At the Saith Point locality the trails are nuaerous, mil preserved and have a turning configuration. Poorly preserved trails are also found near Pugwsh, Carter land County, Nova Scotia. The trails at Smith Point and Pugnaeh are late Nestpnallan In age. These trails are attributed to the giant Carboniferous myrlapod, trthropleur&.